Cover Picture: Materials and Corrosion. 4/2023. Issue 4 (3rd April 2023) - Martinelli‐Orlando, Federico; Dénervaud, Eric; Grange, Rachel; Angst, Ueli
Abstract : Cover: Second‐harmonic generation (SHG) was used to monitor in‐situ compositional changes to carbon steel surfaces immersed in aqueous solutions and during electrochemical experiments. For passive film formed on carbon steel samples, the response in SHG intensity showed a peak in presence of Fe3 O4, while it shows a decrease in presence of Fe2 O3 . Upon application of cathodic protection for 30 minutes, SHG response revealed the formation and growth of a Fe3 O4 film on the carbon steel surface. In this work, the results obtained with SHG were compared with in‐situ active reflectance spectroscopy measurements. More detailed information can be found in: Federico Martinelli‐Orlando, Eric Dénervaud, Rachel Grange, Ueli Angst, Second‐harmonic generation technique for in‐situ study of passive film formation on carbon steel surfaces in aqueous solutions, Materials and Corrosion 2023, 74, 508.